Mandatory Human Rights Due Diligence in Germany and Norway: Stepping, or Striding, in the Same Direction? - Krajewski, Markus; Tonstad, Kristel; Wohltmann, Franziska (Business and Human Rights Journal, 2021)
Germany and Norway are the two latest states to adopt laws mandating human rights due diligence by companies. Germany adopted a Law on Supply Chain Due Diligence (German Law) on 10 June 2021.1 The same day, the Norwegian parliament passed a Transparency Act (Norwegian Act) requiring human rights and decent work due diligence.2 Like the French Loi de Vigilance and the Dutch Child Labour Due Diligence Law, these laws provide further momentum for mandatory measures to promote corporate respect for human rights, including future regulations in the European Union (EU). While the aims are similar, the German and Norwegian laws contain certain important differences when it comes to the substance and scope of the due diligence requirement. In this context, adherence to international standards remains the way forward to ensure compliance with divergent requirements in different jurisdictions.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Germany; mandatory human rights due diligence laws; Norway; UNGPs